Debating issues in American education : a Sage reference set - Brady, Kevin P.; Brown, Frank, 1935-2025; Cattaro, Gerald Michael; Donahoo, Saran; Eakle, A. Jonathan, 1957-; Eckes, Suzanne; Hunter, Richard C., Dr.; Lasley, Thomas J.; Osborne, Allan G., Jr., 1951-; Russo, Charles J.; Thro, William E. (Los Angeles ; London : SAGE reference, 2012)
"This issues-based reference set on education in the United States tackles broad, contentious topics that have prompted debate and discussion within the education community. The volumes focus on pre-school through secondary education and explore prominent and perennially important debates. This set is an essential reference resource for undergraduate students within schools of education and related fields including educational administration, educational psychology, school psychology, human development, and more"--Publisher website.
v. 1. Alternative schooling and school choice / Allan G. Osborne, Jr., Charles J. Russo, Gerald M. Cattaro -- v. 2. Curriculum and instruction / A. Jonathan Eakle -- v. 3. Diversity in schools / Frank Brown, Richard C. Hunter, Saran Donahoo -- v. 4. Religion in schools / Charles J. Russo -- v. 5. School discipline and safety / Suzanne E. Eckes, Charles J. Russo -- v. 6. School finance / William E. Thro -- v. 7. School governance / Richard C. Hunter, Frank Brown, Saran Donahoo -- v. 8. School law / Charles J. Russo -- v. 9. Standards and accountability in schools / Thomas J. Lasley, II -- v. 10. Technology in schools / Kevin P. Brady.
"A SAGE Reference publication."
Includes bibliographical references and index.
Keywords: Public schools -- United States; Education -- United States; School choice -- United States; Public schools -- Curricula -- United States; Multicultural education -- United States; Religion in the public schools -- United States; School discipline -- United States; Education -- United States -- Finance; School management and organization -- United States; Educational law and legislation -- United States; Education -- Standards -- United States; Educational technology -- United States -- Planning